Identification of Load Management System on KK Bung Tomo as Passanger Ship R-16 - Arleiny; Moe, Moejino; Damayanto Purba; Mutiara Paulina Latuheru; Renta Novaliana Siahaan (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
Cargo handling systems on pioneer passenger ships are generally designed for efficiency and safety in loading and unloading goods and other cargoes. The following are some of the components that are generally found in the cargo handling system on pioneer passenger ships: among others include Cargo Storage Area, Cargo Handling Equipment, Fastening and Buffer Systems, Labeling and Tracking Systems, Information and Management Systems, Safety and Training Procedures, Routine Maintenance, Overall Cargo Regulation, cargo handling systems on pioneer passenger ships must be designed and operated with regard to efficiency, security, and compliance with applicable maritime regulations. This research was carried out on KM Tomo which implements Route R 16 with 9 ports. This research uses a qualitative method using observation, interview and documentation methods. Primary data is obtained directly by observing and interviewing the Skipper and secondary data is obtained from data collection and documentation.